2016
DOI: 10.1002/celc.201500520
|View full text |Cite
|
Sign up to set email alerts
|

Improved Cycling Stability of Lithium‐Metal Anode with Concentrated Electrolytes Based on Lithium (Fluorosulfonyl)(trifluoromethanesulfonyl)imide

Abstract: A new type of concentrated electrolyte composed of Li[(FSO2)N(SO2CF3)] (LiFTFSI), Li[N(SO2F)2] (LiFSI), and ether solvents can improve the cycling stability of lithium (Li) metal and inhibit Li‐metal dendritic growth. The high average coulombic efficiency of >95 % and excellent cycling performance of >250 cycles for the Li|copper cells have been achieved, even at a high current density of 3 mA cm−2. Moreover, the Li|LiFePO4 cell exhibits superior cycling stability with capacity retention of >92 % at 0.2 C for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 37 publications
2
45
0
6
Order By: Relevance
“…The general strategy in this regard is to tailor the SSE properties so that it can facilitate the pairing of a Li metal anode with a cathode material that can operate at high voltages. While there are a number of challenges in tuning the properties of a SSE to facilitate stable and high capacity cycling of a Li metal anode, great progress has been made in this area over the last decade, particularly with the high concentration sulfonylimide‐based anion liquid electrolytes (FSI, TFSI, and FTFSI) . However, less attention has been devoted to overcoming the set of challenges that are present at the high voltage cathode.…”
Section: Progress and Challenges For Prototyping High Energy Sslbsmentioning
confidence: 99%
“…The general strategy in this regard is to tailor the SSE properties so that it can facilitate the pairing of a Li metal anode with a cathode material that can operate at high voltages. While there are a number of challenges in tuning the properties of a SSE to facilitate stable and high capacity cycling of a Li metal anode, great progress has been made in this area over the last decade, particularly with the high concentration sulfonylimide‐based anion liquid electrolytes (FSI, TFSI, and FTFSI) . However, less attention has been devoted to overcoming the set of challenges that are present at the high voltage cathode.…”
Section: Progress and Challenges For Prototyping High Energy Sslbsmentioning
confidence: 99%
“…208 After this path-breaking work, it was reported that stable Li metal deposition and stripping reactions in HCEs with ether solvents were observed. [209][210][211] At high concentrations, the LiTFSI/DOL+DME electrolyte could not only effectively suppress dendrite formation at the metallic Li negatrode but also inhibit the dissolution of lithium polysulphide, resulting in excellent cycling performance and improved safety. 209 In this case, for unknown reasons, a rather low columbic efficiency of ca.…”
Section: Highly Concentrated Electrolytesmentioning
confidence: 99%
“…Among these, ether-based electrolytes present the highest CE and the lowest overpotential, effectively suppressing dendrite growth owing to their low reactivity with Li metal. 2,4,12,14,17,22,[29][30][31][32][33][34][35] Especially, the highest cycling CE of 99.1% was recently realized in 1,2-dimethoxyethane (DME). 4 However, ether-based electrolytes are intrinsically unstable against oxidation on cathode surfaces, as characterized by their typical anodic limits of <4 V, 36 which is much lower…”
Section: Introductionmentioning
confidence: 99%